PENGARUH VARIASI JENIS STIMULUS INFORMASI PADA MEMORI JANGKA PENDEK - Soufika Zamharira Rokan; Aldy Safruddin Rambe (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2021)
Background: Memory acts as a storage mechanism for obtained knowledge which can be remembered later. Especially for students who spend most of their time to study, short-term memory is often being used before the information consolidated to long-term memory.The past researches have indicated that individual’s attention level whom receive multisensory stimuli will be higher than those who receive unisensory stimulus. In which attenion is closely related to memory, thus stimuli can affect individual’s short-term memory performance Method: This present study is an analytic-experimental study with posttest only design. Short-term memory performance is measured by Digit Span test. Each of the three groups were given three different stimuli namely auditory, visual, and audiovisual. The score would be analyze using one-way ANOVA statistical test. In which the p-value ? 0,05 is considered significant. Results: There is a significant difference of the Digit Span total score among three groups with different stimuli. The p-value is 0.003 on ANOVA test. On Bonferroni statistical test, the audiovisual group obtained the highest score with p-value 0.016 compared to the auditory group and 0.005 compared to the visual group. Discussion: Two stimuli of information provided a better impact on short-term memory than giving one stimulus. This occurs because of the integration in the parietal-temporal-occipital association cortex to two or more stimuli that are given simultaneously. Processing the input received by the brain becomes easier and a more complete memory output is obtained. Conclusion: There is a significant result on this study by giving different type of stimuli towards short-term memory performance